2021
DOI: 10.5812/zjrms.104127
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy and Its Complications

Abstract: Objectives: This study aimed to evaluate the frequency of episiotomy and its early complications in natural vaginal delivery in the maternity ward of Ali Ibn Abitaleb (AS) Hospital in Zahedan from 2014 - 2016. Methods: In this cross-sectional study, which was conducted in 2017, the archives of women who gave birth between 2014 - 2016 were reviewed. Data were collected using information forms and analyzed by SPSS software. Results: Of 418 women were reviewed, the episiotomy rate was 54.5%; there was a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The process of episiotomy surgery results in injury and pain of the perineum. Pain due to episiotomy is higher than that of non-episiotomy [5]. More than 90% of perineal pain can occur on the first day of childbirth, and as many as 88% of pain cases will subside within 2 months after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…The process of episiotomy surgery results in injury and pain of the perineum. Pain due to episiotomy is higher than that of non-episiotomy [5]. More than 90% of perineal pain can occur on the first day of childbirth, and as many as 88% of pain cases will subside within 2 months after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Eskandar et al reported that 65% of perineal tear risks were decreased by the performance of mediolateral episiotomy, which showed an absolute risk reduction of 1.1% [14]. Furthermore, past studies demonstrated that episiotomy was linked to lower APGAR scores [15,16]. Mousavi et al found that mothers who were indicated for episiotomy had infants with significantly lower APGAR scores at both the first and fifth minutes compared to mothers who were not [17].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our own research, it was found that one of the risk factors for an episiotomy is the first labor. Soleimanzadeh et al (2020) found that 90% of Iranian women who had experienced an episiotomy had their first delivery, while for women who did not have an episiotomy, only 4% [ 22 ]. The results of the research by Beyene et al (2020), Rasouli et al (2016), and Aguiar B. et al (2020) also confirm a significant relationship between the first delivery and more frequent performance of episiotomy [ 8 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the episiotomy was significantly more often performed in the group of younger women that were giving birth and city residents. Soleimanzadeh et al (2020) proved that the mean age of mothers who had an episiotomy was significantly lower than that of mothers without an episiotomy [ 22 ]. Aguiar B. et al (2020) came to the same conclusion [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation